2022
DOI: 10.3389/fendo.2022.873189
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Texture Analysis in the Characterization of Cortisol Secreting vs. Non-Secreting Adrenocortical Incidentalomas in CT Scan

Abstract: New radioimaging techniques, exploiting the quantitative variables of imaging, permit to identify an hypothetical pathological tissue. We have applied this potential in a series of 72 adrenal incidentalomas (AIs) followed at our center, subdivided in functioning and non-functioning using laboratory findings. Each AI was studied in the preliminary non-contrast phase with a specific software (Mazda), surrounding a region of interest within each lesion. A total of 314 features were extrapolated. Mean and standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Second, the patients' clinical information, including clinical symptoms related to adrenal gland tumors and hormone secretion levels, were not included in this study. As reported in a previous human study that demonstrated the feasibility of differentiating functional and non-functional adrenal incidentalomas by CT texture analysis, different results could be obtained depending on whether the adrenal gland tumor is functional ( 47 , 48 ). Further studies on the differences in texture features between functional and non-functional adrenal masses would have clinical value.…”
Section: Discussionmentioning
confidence: 93%
“…Second, the patients' clinical information, including clinical symptoms related to adrenal gland tumors and hormone secretion levels, were not included in this study. As reported in a previous human study that demonstrated the feasibility of differentiating functional and non-functional adrenal incidentalomas by CT texture analysis, different results could be obtained depending on whether the adrenal gland tumor is functional ( 47 , 48 ). Further studies on the differences in texture features between functional and non-functional adrenal masses would have clinical value.…”
Section: Discussionmentioning
confidence: 93%